2015
DOI: 10.4103/0975-1475.172436
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric forensics - Part 2 "Prevalence of elder abuse and their potential forensic markers among medical and dental patients"

Abstract: Context:This study is a continuation of the earlier studies and has been extended to investigate the potential forensic markers of elder abuse.Aims:To determine the prevalence of elder abuse in various outpatient departments (OPDs). To study the associated parameters related to the abuser and the abused. To determine the existence of potential forensic markers of elder abuse.Settings and Design:The subjects were randomly selected from the medical and the dental OPDs of the university.Materials and Methods:Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(23 reference statements)
0
5
1
1
Order By: Relevance
“…Alternatively, they may suppress their negative feelings in front of the patient, whereas blood relatives may unreservedly express their emotions. In contrast to our findings, Mattoo et al . reported that the incidence of abusive behaviour by daughters‐in‐law in India was about the same as that for sons.…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, they may suppress their negative feelings in front of the patient, whereas blood relatives may unreservedly express their emotions. In contrast to our findings, Mattoo et al . reported that the incidence of abusive behaviour by daughters‐in‐law in India was about the same as that for sons.…”
Section: Discussioncontrasting
confidence: 99%
“…Yapılan çalışmalarda da istismar ile cinsiyet arasında anlamlı bir ilişki olduğu bulunmuştur 15,18 . Kadın olmak, her yaş döneminde olduğu gibi yaşlılıkta da ihmal ve istismar açısından önemli bir risk faktörüdür 13,15,[32][33][34] . Özellikle düşük eğitim düzeyine sahip, yalnız ve kırsalda yaşayan kadınların istismara maruz kalma ihtimalinin daha yüksek olduğu bildirilmiştir 20 .…”
Section: Cinsiyetunclassified
“…EA in any of its forms has been shown to impact the victims’ quality of life, and health (medical complications) [ 13 ], and even considered as a serious risk of mortality in medical forensics [ 14 ]. Psychological stress inflicted by EAN has been strongly associated with the development of depression [ 15 ] in elderly subjects.…”
Section: Introductionmentioning
confidence: 99%